Symbolism and Theme as Intrinsic Elements in Robert Frost’s “The Road Not Taken”: A Semiotic Analysis - Irawan, Nafdi; Afriana, Afriana (Asosiasi Ide Bahasa Kepri, 2025)
This study investigates the use of symbolism in Robert Frost’s poem The Road Not Taken and its function in constructing the poem’s central theme. Employing a semiotic analysis grounded in Peirce’s theory of signs, the research identifies and interprets fifteen symbolic elements distributed across the poem’s four stanzas. These symbols such as “two roads,” “yellow wood,” “grassy path,” and “sigh” convey the psychological and philosophical dimensions of decision-making, uncertainty, and the retrospective construction of meaning. Findings demonstrate that Frost’s poetic imagery serves not only as aesthetic expression but also as a medium for exploring existential concerns. The study highlights how literary symbols can effectively mediate complex human experiences and offers insight into the cognitive and emotional processes behind life choices. The results contribute to a deeper understanding of symbolic narrative in poetry and encourage further semiotic research within literary studies.